Peningkatan Pemahaman Masyarakat Pondok Pesantren Al Kirom Hajimena terhadap Undang-Undang Nomor 18 Tahun 2019 tentang Pesantren - Fakih, M.; Natamiharja, Rudi; Setiawan, Ikhsan; Panjaitan, Oksha Dwi Anugrah (Jurnal Nusantara Mengabdi, 2024)
Purpose: This research aims to enhance the understanding of the Al Kirom Hajimena Islamic Boarding School community regarding the recently enacted Pesantren Law. Methodology: To achieve the objectives of this research, a multi-phase approach will be utilized, encompassing preliminary surveys, focus group discussions (FGDs), educational workshops, and post-intervention evaluations. Results: Following the implementation of Focus Group Discussions (FGDs) and educational workshops, a notable improvement in legal understanding among participants was observed. The active participation in FGDs helped identify critical knowledge gaps, while the workshops provided in-depth explanations that addressed existing concerns and confusion. Limitations: This research is within the scope of national law. Contribution: Al Kirom Hajimena Islamic Boarding School.